Long-Term Follow-Up of Patients with Advanced Colorectal Liver Metastasis: A Survival Analysis from the Randomized Controlled Multicenter Trial LIGRO - Dennis Björk, MD; Kristina Hasselgren, MD, PhD; Bård I. Røsok, MD, PhD; Peter N. Larsen, MD, PhD; Ernesto Sparrelid, MD, PhD; Gert Lindell, MD, PhD; Nicolai A. Schultz, MD, PhD; Bjorn A. Bjørnbeth, MD, PhD; Bengt Isaksson, MD, PhD; Anna Lindhoff Larsson, RN; Magnus Rizell, MD, PhD; Bergthor Björnsson, MD, PhD; et al. (Annals of Surgery Open)
Objective:. The objective of this study was to evaluate the long-term oncological outcomes of patients with colorectal liver metastasis (CRLM) randomized for associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) or 2-stage hepatectomy (TSH). Introduction:. For advanced CRLM, TSH or ALPPS may be needed for tumor freedom. The randomized, controlled, multicenter trial LIGRO showed an increased resection rate in patients who underwent ALPPS but no difference in morbidity or mortality. The 2-year survival analysis revealed better overall survival in the ALPPS group. Here, the long-term survival analysis from the LIGRO trial is reported. Methods:. In the LIGRO trial, 100 patients were randomized to TSH or ALPPS, with the option of rescue ALPPS if insufficient growth was found after the initial step of TSH. Patients were enrolled between June 2014 and August 2016. Follow-up data for this study were collected between November 2022 and February 2023. Results:. In total, 16 patients were alive at the end of the follow-up period. The estimated median follow-up time was 93 months. Estimated median overall survival times were 45 months in the ALPPS group and 27 months in the TSH group (P = 0.057), with 5-year survival rates of 31% and 20%, respectively. Positive prognostic factors were liver tumor-free status at the first follow-up and rectal primary tumor. Negative prognostic factors were extrahepatic disease and increasing CLRM size. Conclusion:. Liver tumor-free status is a predictor of long-term survival, along with extrahepatic disease, large CRLM size, and rectal primary tumor. Survival did not significantly differ between patients treated with ALPPS or TSH.